Short-term tagging mortality of Baltic cod (Gadus morhua) - Haase, Stefanie; McQueen, Kate; Mion, Monica; Andersson, Magnus; Hilvarsson, Annelie; Olesen, Hans Jakob; Svenson, Anders; Casini, Michele; Hüssy, Karin; Radtke, Krzysztof; Krumme, Uwe (Fisheries Research, 2021)
Tagging-induced mortality experiments are an important component of mark-recapture studies, as they can be used to assess the appropriateness of the tagging methodology, and to improve the reliability of estimates of recapture rates used for calculations of mortality rates and population size. Here, short-term tagging mortality of Baltic cod was estimated through containment experiments in the southern Baltic Sea. Experimental cod were selected from trawl catches, and approximately half were tagged externally with T-bar tags and received an intraperitoneal injection of tetracycline-hydrochloride. The rest of the experimental cod formed the control group, and received neither tag nor injection. The tagged and control cod were mixed evenly within submersible cages, and held for 5− 8 days. The experiments were conducted in different regions and during different months by different tagging teams. Overall mortality rate was 16 % (n =324), with the mortality rate of the tagged group 19 %, and the mortality rate of the control group 13 %. A general linear mixed model was fit to assess the effect of tagging, month, experiment duration, fish length and tagging site (i.e. the combined effect of region and tagging team) on mortality. Tagging had no effect on mortality, indicating that mortality can be attributed mainly to the capture and handling procedure. There was a significantly negative relationship between fish length (range: 20− 55cm) and mortality. Mortality did not differ between the months tested, but there was a significant effect of tagging site on mortality. Tagging-related mortality should be accounted for in analyses of data from mark-recapture studies of Baltic cod, and some variability in mortality between tagging sites can be expected